The First Geogarypid (Pseudoscorpiones, Geogarypidae) in Rovno Amber (Ukraine) - Henderickx, H.; Perkovsky, E.E. (Вестник зоологии, 2012)
The first Geogarypus found in Rovno amber appears to be conspecific with Geogarypus gorskii Henderickx 2005, a species known from Eocene Baltic amber.